Sakhalin coal mines as factor in development of Russian Far East. The second half of XIX c. - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
An important factor in the development and retention of the region is availability of energy resources on its territory. They facilitate the development and maintenance of military infrastructure, it enables the effective development of transport and industry. The article examines the experience of using coal mines of Sakhalin Island to supply the Siberian Flotilla and the creation of the Sakhalin Society, which was supposed to solve the energy, economic and demographic problems of the region. The author analyzes the reasons for the failure of the Russian administration’s attempts to use Sakhalin’s coal deposits as an alternative to buying coal in foreign countries